2015
DOI: 10.3390/ijms161126041
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes in the Inflammatory Nociceptive Behavior of Mice

Abstract: The processing of pain undergoes several changes in aging that affect sensory nociceptive fibers and the endogenous neuronal inhibitory systems. So far, it is not completely clear whether age-induced modifications are associated with an increase or decrease in pain perception. In this study, we assessed the impact of age on inflammatory nociception in mice and the role of the hormonal inhibitory systems in this context. We investigated the nociceptive behavior of 12-month-old versus 6–8-week-old mice in two be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Others have reported a similar absence of thermal hyperalgesia in LBP models 35 . The absence of thermal sensitivity may be related to a loss of TRPV1 expression reported as early as one year in mouse spinal cords 103 .…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported a similar absence of thermal hyperalgesia in LBP models 35 . The absence of thermal sensitivity may be related to a loss of TRPV1 expression reported as early as one year in mouse spinal cords 103 .…”
Section: Discussionmentioning
confidence: 99%
“…Animals were bred and maintained following National Health Service guidelines [22]. In behavioral experiments, 40 CD1 females between 6 and 8 weeks of age were employed, as at this age pain sensitivity is higher than in older mice [23] and thus the efficacy of analgesic treatment is more evident. Animals were divided into four categories, with 10 animals in each group: (a) vehicle injection (PBS) without PBM, (b) capsaicin injection without PBM, (c) capsaicin injection with PBM at WL 1, (d) capsaicin injection with PBM at WL 2.…”
Section: Murine Model Of Nociceptionmentioning
confidence: 99%
“…Both of these well-characterized behaviors are easy to measure and can reveal information about age-dependent changes in central and peripheral nociceptive modulation. Previous studies have revealed conflicting changes in spontaneous formalin behavior in both mice and rats, but no study has yet investigated if age affects mechanical sensitivity following formalin injection (Gagliese and Melzack, 2000; King-Himmelreich et al, 2015). …”
Section: Introductionmentioning
confidence: 99%